Optimal Control Analysis of a Human-Animal Nipah Virus Transmission Model - Ratna Widayati; Ramya Rachmawati; Yulian Fauzi; Septri Damayanti; Arlin Marsyanda (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2026)
This study proposes a novel multi-host SIRS optimal control model for Nipah virus transmission involving bats, pigs, and humans, extending classical SIR/SEIR frameworks by explicitly incorporating cross-species transmission, reinfection, and heterogeneous contact pathways supported by ecological evidence. Unlike uncontrolled epidemic models, the proposed framework integrates three time-dependent interventions: infected-pig culling, human–animal protective measures, and isolation of infected humans, allowing simultaneous evaluation of epidemiological impact and implementation cost. The existence of an optimal control set is established, and Pontryagin’s Maximum Principle is applied to derive the necessary optimality system. Numerical simulations show that coordinated interventions substantially outperform no-control scenarios. The peak number of infected humans decreases from more than 650,000 to approximately 70,000, while the peak number of infected pigs declines from over 68,000 to about 16,000. Control trajectories indicate that strong early implementation of all measures is the most effective strategy, followed by gradual relaxation as prevalence declines, leading to more efficient resource allocation over time. Compared with classical single-host SIR/SEIR models, the proposed model better captures interspecies spillover dynamics and enables evaluation of integrated response policies that cannot be represented in simpler frameworks. These findings demonstrate the importance of coordinated multi-component strategies for mitigating Nipah outbreaks across interacting host populations. A limitation of this study is the use of assumed parameter values in several transmission processes; future work may incorporate data-driven calibration, stochastic effects, spatial mobility, and uncertainty analysis to improve predictive accuracy. AbstrakPenelitian ini mengusulkan model optimal kontrol SIRS multi-host yang baru untuk penularan virus Nipah yang melibatkan kelelawar, babi, dan manusia, sebagai pengembangan dari kerangka klasik SIR/SEIR dengan secara eksplisit memasukkan penularan antarspesies, reinfeksi, serta jalur kontak heterogen yang didukung oleh bukti ekologis. Berbeda dengan model epidemi tanpa kontrol, kerangka yang diusulkan mengintegrasikan tiga intervensi bergantung waktu, yaitu pemusnahan babi terinfeksi, tindakan perlindungan manusia–hewan, dan isolasi manusia terinfeksi, sehingga memungkinkan evaluasi simultan terhadap dampak epidemiologis dan biaya implementasi. Keberadaan himpunan kontrol optimal dibuktikan, dan Prinsip Maksimum Pontryagin diterapkan untuk menurunkan sistem syarat optimalitas yang diperlukan. Simulasi numerik menunjukkan bahwa intervensi terkoordinasi secara signifikan lebih unggul dibandingkan skenario tanpa kontrol. Puncak jumlah manusia terinfeksi menurun dari lebih dari 650.000 menjadi sekitar 70.000, sedangkan puncak babi terinfeksi turun dari lebih dari 68.000 menjadi sekitar 16.000. Profil kontrol menunjukkan bahwa penerapan kuat pada tahap awal untuk seluruh tindakan merupakan strategi paling efektif, kemudian dikurangi secara bertahap seiring menurunnya prevalensi sehingga menghasilkan alokasi sumber daya yang lebih efisien dari waktu ke waktu. Dibandingkan model klasik SIR/SEIR satu-host, model yang diusulkan lebih mampu menggambarkan dinamika spillover antarspesies serta mengevaluasi kebijakan respons terpadu yang tidak dapat direpresentasikan pada model yang lebih sederhana. Temuan ini menegaskan pentingnya strategi multi-komponen yang terkoordinasi dalam mitigasi wabah Nipah pada populasi host yang saling berinteraksi. Keterbatasan penelitian ini adalah penggunaan beberapa nilai parameter asumsi pada proses transmisi tertentu; penelitian selanjutnya dapat memasukkan kalibrasi berbasis data, efek stokastik, mobilitas spasial, dan analisis ketidakpastian untuk meningkatkan akurasi prediksi.Kata Kunci: Penularan antarspesies; Nipah virus; Kontrol optimal; Dinamika populasi; Model SIRS. 2020MSC: 49J15